Assessment Development Level of Agriculture in Iran's Provinces Utilizing Factor Analysis and Numerical Taxonomy - Jafar Tavakkoli (جغرافیا و پایداری محیط)
This research investigates agricultural development level of Iran’s provinces on the basis of 35 agriculture development indicators (infrastructural, institutional, manpower, mechanization and productivity) utilizing combined method of factor analysis and numerical taxonomy. The results indicate that despite of natural conditions’ effect, development level of countries’ regions to a large extent affected by human and managerial factors. Hence some provinces with appropriate natural capacities ranked as less-developed and non-developed in regard of agriculture development. Considering that sum of minimum gaps for East Azerbaijan equals to 4.51 and is more than upper threshold of homogeneity [d(+) = 4.331], this province is heterogeneous to others but in regard of agriculture development placed on the best condition. Furthermore among homogeneous provinces, Mazandaran, Isfahan, Chaharmahal & Bakhtiari and Tehran in regard of agriculture development level (DL< 0.7001) acquired first to fourth position in ranking. In addition Ghazvin, southern khorasan, khosestan and Sistan & Baluchestan one after the other, in respect of agriculture development level (DL > 0.9302) placed in twenty-sixth to twenty-ninth position. So for reducing regions and provinces agricultural development inequalities, approaching regional and local planning and taking into account balanced resources allocation, capacity assessment studies, production professionalism and attracting internal and external investors can be useful.